2021
DOI: 10.1038/s41598-021-83589-z
|View full text |Cite
|
Sign up to set email alerts
|

The interaction on hypertension between family history and diabetes and other risk factors

Abstract: To explore the individual effect and interaction of diabetes and family history and other risk factors on hypertension in Han in Shanghai China. The method of case–control study with l:l matched pairs was used, 342 cases of hypertension and 342 controls were selected and investigate their exposed factors with face-to-face. The method of epidemiology research was used to explore the individual effect and interaction of diabetes and family history and other risk factors on hypertension. The individual effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 26 publications
4
24
0
1
Order By: Relevance
“…Moreover, T2DM with hypertension has been regarded as an independent risk factor for severe organ involvement [ 8 ]. Growing evidence has demonstrated that hypertension and T2DM usually occurred successively [ 9 ], and compared with normotensive individuals, hypertensive individuals were 2.5 times more likely to develop T2DM within 5 years [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, T2DM with hypertension has been regarded as an independent risk factor for severe organ involvement [ 8 ]. Growing evidence has demonstrated that hypertension and T2DM usually occurred successively [ 9 ], and compared with normotensive individuals, hypertensive individuals were 2.5 times more likely to develop T2DM within 5 years [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 15 interviews were conducted with 9 women and 6 men. The median age was 44 years (range 35-49) for men and 37 (range [35][36][37][38][39][40][41][42][43][44][45] for women. Participants' occupations were substance agriculture/farming (4) (small scale farmers producing largely for their home use), trader/vendor/shopkeepers (5), fisherfolk (2), government/clerical workers (2), restaurant/waiter (1) and a housewife (1).…”
Section: Resultsmentioning
confidence: 99%
“…Family history of hypertension was a crucial marker of genetic factors, it was used as an alternative indicator to study the relationship between genetic factors and diseases frequently ( 36 ). The speedy economic growth, especially with a higher dietary salt intake, was another new and crucial factor related to the increased prevalence of hypertension in China, and quite a few lines of proof that include epidemiological observations, animal studies, and clinical trials have constantly proven a causal relationship between dietary salt consumption and hypertension ( 37 , 38 ). Excess dietary salt consumption was also an essential risk factor for the development and progression of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%